Hydraulic axis actuation control for precision motion. (27th January 2009) - El-Shalabi, S.; Ebrahimi, M.; Mason, B.; Whalley, R., A.A. Ameer
A new design for machine tool axis traverse, by hydraulic cylinder with spool and needle valve actuators, is presented. Regulation procedures enabling the formulation of a least effort control strategy are proposed. System integrity in the event of actuator failure is examined. Correspondingly, the maintenance of closed-loop stability, following feedback transducer loss, is also secured, demonstrating fail-safe, multivariable and feedback control. The suppression of the effects of disturbances and the response of the system to deterministic inputs is presented. Comments on the practicality of the design are incorporated and the mandatory specification of control system integrity is advocated.